PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Students' Journal of Accounting and Banking, 2013)
The objective of this study is to examine The Effect Of Good Corporate Governance and Corporate Social Responsibility To The Value Firm. Good Corporate Governance measured by of institutional ownership, managerial ownership, independence commissioners, auditors quality, audit committee. Corporate Social Responsibility measured by CSR index while the value firm measured by Price to Book Value (PBV). The sample was 20 companies chosen by using purposive sampling method. While for the technique of testing the data  the writer used multiple linear regression. The result indicates that auditors quality and audit committee are significant positively to the firm value. Institutional ownership, managerial ownership, independence of commissioners and corporate social responsibility are significant negatively to the firm value. Keywords: Good Corporate Governance, Corporate Social Responsibility and value firm.